Analysis of underground rock cavern in the vicinity of a fault - Chua, Alicia Jing Wen (2017)
Underground development has become a more increasingly considered solution for the limited land space in Singapore. The purpose of this study is to investigate the factors that may affect the stability of the rock cavern where fault lines are located its vicinity.